Asymptomatic Bone Cement Pulmonary Embolism after Vertebroplasty: Case Report and Literature Review. (7th May 2013) - Geraci, Girolamo; Lo Iacono, Giorgio; Lo Nigro, Chiara; Cannizzaro, Fabio; Cajozzo, Massimo; Modica, Giuseppe
Abstract : Introduction . Acrylic cement pulmonary embolism is a potentially serious complication following vertebroplasty. Case Report . A 70-year-old male patient was treated with percutaneous vertebroplasty for osteoporotic nontraumatic vertebral collapse of L5-S1. Asymptomatic pulmonary cement embolism was detected on routine postoperative chest radiogram and the patient was treated with enoxaparin, amoxicillin, and dexamethasone. At the followup CT scan no further migration of any cement material was reported; and the course was uneventful. Discussion . The frequency of local leakage of bone cement is relatively high (about 80–90%), moreover, the rate of cement leakage into the perivertebral veins (seen in up to 24% of vertebral bodies treated) with consequent pulmonary cement embolism varies from 4.6 to 6.8% (up to 26% in radiologic studies); the risk of embolism is increased with the liquid consistency of the cement and with the treatment of some malignant lesions. Patients may remain asymptomatic and develop no known long-term sequelae. Conclusions . Our ancedotal case illustrates the need for close monitoring of patients undergoing percutaneous vertebroplasty and emphasizes the importance of prompt and correct diagnosis and treatment, even if actually there is no agreement regarding the therapeutic strategy.